2020
DOI: 10.3390/app11010261
|View full text |Cite
|
Sign up to set email alerts
|

Track Modulus Assessment of Engineered Interspersed Concrete Sleepers in Ballasted Track

Abstract: Ballasted railway track is typically constructed using sleepers that are manufactured from a common material type within a given length of track. Timber and concrete are the two most common sleeper materials used internationally. Evidence from historical installations of interspersed concrete sleepers in timber sleeper track in North America has indicated inadequate performance, due largely to the heterogeneity in stiffnesses among sleepers. Theoretical calculations reveal that interspersed installation, assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Lima et al [12] evaluated that railway-engineered interspersed concrete (EIC) sleepers can successfully replicate the stiffness of timber sleepers installed in tracks using field instrumentation installed under revenue-service train operations on a North American commuter rail transit agency to measure the wheel-rail vertical loads and track displacement. The results indicated that there are minimal differences in median track displacements between timber (2.26 mm, 0.089 in.)…”
Section: Insights Into Systems Behavioursmentioning
confidence: 99%
“…Lima et al [12] evaluated that railway-engineered interspersed concrete (EIC) sleepers can successfully replicate the stiffness of timber sleepers installed in tracks using field instrumentation installed under revenue-service train operations on a North American commuter rail transit agency to measure the wheel-rail vertical loads and track displacement. The results indicated that there are minimal differences in median track displacements between timber (2.26 mm, 0.089 in.)…”
Section: Insights Into Systems Behavioursmentioning
confidence: 99%
“…Previous studies have shown that the interspersed method is more economical than fully replacing aged timber sleepers [ 9 ]. The interspersed railway systems have enough track quality to operate with a considerable train speed under normal weather conditions [ 13 , 14 , 15 , 16 , 17 , 24 ]. Nevertheless, the approach would result in inconsistent track stiffness due to the elasticity difference between the renewed concrete sleepers and the unreplaced aged timber sleepers [ 15 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These sensors do not require significant modification to track components during the installation process. Over the past few decades, research on strain-gauge-based systems for track response monitoring has been noticeable ( 133 ). Although the use of strain-gauge-based systems for train-induced wheel-load measurement is relatively common, only a few studies have recently reported the use of these systems for rail–tie interaction force measurement ( 2, 5, 7, 9, 13, 14, 26, 27, 2933 ).…”
Section: Introductionmentioning
confidence: 99%